2012
DOI: 10.1115/1.4007310
|View full text |Cite
|
Sign up to set email alerts
|

A New Extended Multiple Car-Following Model Considering the Backward-Looking Effect on Traffic Flow

Abstract: To make full use of the newly available information provided by the intelligent transportation system (ITS), we presented a new car-following model applicable to automated driving control, which will be realized in the near future along with the rapid development of ITS. In this model, the backward-looking effect and the information inputs from multiple leading cars in traffic flow are considered at the same time. The linear stability criterion of this model is obtained using linear stability theory. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
0
9
1
2
Order By: Relevance
“…As R V ≤ 0, γ 2 contributes positively to the left hand side of equation (28) which consequently destabilizes traffic flow, which is in contradiction to the findings in literature (Nakayama, Sugiyama, and Hasebe 2001;Ge, Zhu, and Dai 2006b;Sun, Liao, and Peng 2011;Yang et al 2013), where it was found that backward looking strategy improves the linear stability condition. These results will be illustrated numerically in Section 5 for different sets of model parameters.…”
Section: Linear Stability Conditionscontrasting
confidence: 55%
See 2 more Smart Citations
“…As R V ≤ 0, γ 2 contributes positively to the left hand side of equation (28) which consequently destabilizes traffic flow, which is in contradiction to the findings in literature (Nakayama, Sugiyama, and Hasebe 2001;Ge, Zhu, and Dai 2006b;Sun, Liao, and Peng 2011;Yang et al 2013), where it was found that backward looking strategy improves the linear stability condition. These results will be illustrated numerically in Section 5 for different sets of model parameters.…”
Section: Linear Stability Conditionscontrasting
confidence: 55%
“…In literature, the backward looking effect has been considered using the OVM or FVDM (Nakayama, Sugiyama, and Hasebe 2001;Ge, Zhu, and Dai 2006b;Sun, Liao, and Peng 2011;Yang et al 2013). Based on the bidirectional looking framework of Jin et al (2014) which considered the acceleration to consist of two tasks: backward looking and forward looking strategy, Zheng, Jin, and Huang (2015) proposed a bidirectional microscopic model using the Helly car-following model (Helly 1959):…”
Section: Multi-anticipative Bidirectional Microscopic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have not only reported enhanced traffic flow efficiency because of cooperation and exchange of information between vehicles (e.g. Monteil, Nantes, Billot, Sau, & El Faouzi, 2014;Wang, Daamen, Hoogendoorn, & van Arem, 2016b;Xie, Zhang, Gartner, & Arsava, 2016;Yang, Liu, Sun, & Li, 2013;Zhou, Qu, & Jin, 2016) but also between vehicles and infrastructure (e.g. variable speed limits, see Grumert, Ma, & Tapani, 2015;Wang, Daamen, Hoogendoorn, & van Arem, 2016a).…”
Section: Literature Resultsmentioning
confidence: 99%
“…In multianticipative models [8][9][10], the relative current is the current difference of the two adjacent sites ahead. This is similar to the idea in the multianticipative car-following models [11][12][13][14].…”
Section: Introductionmentioning
confidence: 54%